A Hybrid Method for Dynamic Mesh Generation Based on Radial Basis Functions and Delaunay Graph Mapping (Advances in Applied Mathematics and Mechanics, 2018)
Aiming at complex configuration and large deformation, an efficient hybridmethod for dynamic mesh generation is presented in this paper, which is based onRadial Basis Functions (RBFs) and Delaunay graph mapping. Based on the computationalmesh, a set of very coarse grid named as background grid is generated firstly,and then the computational mesh can be located at the background grid by Delaunaygraph mapping technique. After that, the RBFs method is applied to deform the backgroundgrid by choosing partial mesh points on the boundary as the control points.Finally, Delaunay graph mapping method is used to relocate the computational meshby employing area or volume weight coefficients. By applying different dynamic meshmethods to a moving NACA0012 airfoil, it can be found that the RBFs-Delaunay graphmapping hybrid method is as accurate as RBFs and is as efficient as Delaunay graphmapping technique. Numerical results show that the dynamic meshes for all test casesincluding one two-dimensional (2D) and two three-dimensional (3D) problems withdifferent complexities, can be generated in an accurate and efficient manner by usingthe present hybrid method.